Analisis Fitokimia Hasil GC-MS Parmelia sulcata (Ascomycota : Parmeliaceae) Sebagai Pewarna Alami - Muzzazinah Muzzazinah; Awanda Elrita Putri; Nurmiyati Nurmiyati; Alanindra Saputra (Jurnal Ilmiah Sains, 2025)
A Parmelia sulcata is the largest family of lichen fungi, consisting of around 2,700 species spread across 80 countries. Lichen is an organism resulting from symbiosis between fungi and algae. This research aims to analyze the phytochemical results and find out whether Parmelia sulcata has potential as a natural dye to be applied to natural fiber fabrics. The research location is Tanen Village, Kemuning, Ngargoyoso, Central Java. Sample exploration was carried out using the exploration method, the samples were analyzed using GC-MS, where from the GC-MS results there were various compounds, therefore the researchers wanted to provide laboratory test data regarding the chemical content of the Parmelia sulcata species. Phytochemical and GC-MS test results are as follows: 3,5-Dihydroxytoluene 33.77%; 2-[3' Hydroxypropyl]-1,4-Benzenediol 3.32%; 1,3-Benzenediol, 2-Methyl 3.75%; Resorcyclic Beta Acid, 6-Methyl, Methyl Ester 1.43%; Resorcyclic Beta Acid, 6-Methyl, Methyl Ester 8.56%; 3-Cyclohexene-1-Methanol,6-1(1-Hydroxycyclopentyl)-, Cis 1.91%; Resorcyclic Beta Acid, 6-Methyl, Methyl Ester 37.15%; Acetonitrile, 9h-Pyrolo[1,2-A] Indole-9-Ylidene 1.00%; Fluoranthene-2-Carboxaldehyde 3.62%, this shows that Parmelia sulcata has less potential to be used as a natural dyes. Keywords: Phytochemistry; Compound Content; Parmelia sulcata; Natural Dyes